Structural engineers' handbook data for the design and construction of steel bridges and buildings - Ketchum, Milo S. 1872-1934 (McGraw-Hill, 1924)
This book offers data, details and tables for the design and construction of steel bridges and buildings. Data and tables that will be of service to the designing and constructing engineer have been given, rather than predigested data and designs that might be used by the untrained.